Poems of Nazim Hikmet - Ran, Nâzım Hikmet, 1902-1963. (New York)
xviiii 274 sayfa
Keywords: “This second edition of “Poems of Nazim Hikmet“, revised and expanded on the occasion of the poet's centennial, features his one hundred best poems, chosen from the length of his forty-year career and presented in the widely acclaimed English versions that have made him such an influential presence in contemporary poetry for the past quarter-century. The first and foremost modern Turkish poet, Hikmet (1902-1963) served a thirteen-year sentence as a political prisoner in his native Turkey and spent his last thirteen years in exile. Banned is his own country for thirty years, his poetry has been translated into more than fifty languages, and today he is recognized around the world as one of the essential poets of the twentieth century“ --